International diversification and the Irish economy - Lane, Philip R. (Economic & Social Studies, 2000)
We take an initial step in investigating the international diversification of Irish production risk. We find evidence that Ireland displays some properties associated with international risksharing. These include: high gross stocks of foreign assets and liabilities; high international consumption correlations relative to output correlations; and pro-cyclical behaviour of the yield on net external liabilities.
Keywords: International diversification; Irish economy; Production risk; Risk diversification; Open economy; Ireland